Clinical Impact of an Electronic Dashboard and Alert System for Sedation Minimization and Ventilator Liberation: A Before-After Study. (October 2019) - Anderson, Brian J.; Do, David; Chivers, Corey; Choi, Katherine; Gitelman, Yevgeniy; Mehta, Shivan J.; Panchandam, Venkat; Gudowski, Steve; Pierce, Margie; Cereda, Maurizio; Christie, Jason D.; Schweickert, William D.; et al.
Abstract : Objectives: Sedation minimization and ventilator liberation protocols improve outcomes but are challenging to implement. We sought to demonstrate proof-of-concept and impact of an electronic application promoting sedation minimization and ventilator liberation. Design: Multi-ICU proof-of-concept study and a single ICU before-after study. Setting: University hospital ICUs. Patients: Adult patients receiving mechanical ventilation. Interventions: An automated application consisting of 1) a web-based dashboard with real-time data on spontaneous breathing trial readiness, sedation depth, sedative infusions, and nudges to wean sedation and ventilatory support and 2) text-message alerts once patients met criteria for a spontaneous breathing trial and spontaneous awakening trial. Pre-intervention, sedation minimization, and ventilator liberation were reviewed daily during a multidisciplinary huddle. Post-intervention, the dashboard was used during the multidisciplinary huddle, throughout the day by respiratory therapists, and text alerts were sent to bedside providers. Measurements and Main Results: We enrolled 115 subjects in the proof-of-concept study. Spontaneous breathing trial alerts were accurate (98.3%), usually sent while patients were receiving mandatory ventilation (88.5%), and 61.9% of patients received concurrent spontaneous awakening trial alerts. We enrolled 457 subjects in the before-after study, 221 pre-intervention and 236 post-intervention. After implementation, patients were 28% more likely to be extubated (hazard ratio, 1.28; 95% CI, 1.01–1.63; p = 0.042) and 31% more likely to be discharged from the ICU (hazard ratio, 1.31; 95% CI, 1.03–1.67; p = 0.027) at any time point. After implementation, the median duration of mechanical ventilation was 2.20 days (95% CI, 0.09–4.31 d; p = 0.042) shorter and the median ICU length of stay was 2.65 days (95% CI, 0.13–5.16 d; p = 0.040) shorter, compared with the expected durations without the application. Conclusions: Implementation of an electronic dashboard and alert system promoting sedation minimization and ventilator liberation was associated with reductions in the duration of mechanical ventilation and ICU length of stay. Abstract : Supplemental Digital Content is available in the text.